The Relationship between Unemployment and Risk-Aversion - Luis Diaz-Serrano; Donal O'Neill (Institute for the Study of Labor (IZA), 2004)
In this paper we use a direct measure of individual risk-aversion to examine the relationship between risk-aversion and unemployment. The traditional search model predicts that more risk-averse individuals have lower reservation wages and thus are less likely to be observed in unemployment. Our findings, however, do not support this prediction: on the contrary our data suggest that more risk-averse individuals are more likely to be unemployed.
Keywords: J64; 330; unemployment; job-search; risk-aversion; Arbeitslosigkeit; Arbeitsuche; Risikoaversion; Schätzung; Italien